Sex disparities in the presentation, management and outcomes of patients with acute coronary syndrome: insights from the ACS QUIK trial. Issue 1 (27th January 2021) - Khraishah, Haitham; Alahmad, Barrak; Alfaddagh, Abdulhamied; Jeong, Sun Young; Mathenge, Njambi; Kassab, Mohamad Bassam; Kolte, Dhaval; Michos, Erin D; Albaghdadi, Mazen
Abstract : Aims: Our aim was to explore sex differences and inequalities in terms of medical management and cardiovascular disease (CVD) outcomes in a low/middle-income country (LMIC), where reports are scarce. Methods: We examined sex differences in presentation, management and clinical outcomes in 21 374 patients presenting with acute coronary syndrome (ACS) in Kerala, India enrolled in the Acute Coronary Syndrome Quality Improvement in Kerala trial. The main outcomes were the rates of in-hospital and 30-day major adverse cardiovascular events (MACEs) defined as composite of death, reinfarction, stroke and major bleeding. We fitted log Poisson multivariate random effects models to obtain the relative risks comparing women with men, and adjusted for clustering by centre and for age, CVD risk factors and cardiac presentation. Results: A total of 5191 (24.3%) patients were women. Compared with men, women presenting with ACS were older (65±12 vs 58±12 years; p<0.001), more likely to have hypertension and diabetes. They also had longer symptom onset to hospital presentation time (median, 300 vs 238 min; p<0.001) and were less likely to receive primary percutaneous coronary intervention for ST-elevation myocardial infarction (45.9% vs 49.8% of men, p<0.001). After adjustment, women were more likely to experience in-hospital (adjusted relative risk (RR)=1.53; 95% CI 1.32 to 1.77; p<0.001) and 30-day MACE (adjusted RR=1.39; 95% CI 1.23 to 1.57, p<0.001). Conclusion: Women presenting with ACS in Kerala, India had greater burden of CVD risk factors, including hypertension and diabetes mellitus, longer delays in presentation, and were less likely to receive guideline-directed management. Women also had worse in-hospital and 30-day outcomes. Further efforts are needed to understand and reduce cardiovascular care disparities between men and women in LMICs.